Diagnostic performance of ultrasonography in pre-operative assessment of lymph nodes in patients with cervical cancer - Fruhauf, Filip; Cibula, David; Kocian, Roman; Zikan, Michal; Dundr, Pavel; Jarkovsky, Jiri; Fischerova, Daniela (International journal of gynecological cancer : official journal of the International Gynecological Cancer Society, 2024)
OBJECTIVES: To assess the diagnostic performance of ultrasonography in pre-operative assessment of lymph nodes in patients with cervical cancer, to compare the outcomes for pelvic and para-aortic regions, and to detect macrometastases and micrometastases separately. METHODS: Patients were retrospectively included if they met the following inclusion criteria: pathologically verified cervical cancer; ultrasonography performed by one of four experienced sonographers; surgical lymph node staging, at least in the pelvic region-sentinel lymph node biopsy or systematic pelvic lymphadenectomy or debulking. The final pathological examination was the reference standard. RESULTS: 390 patients met the inclusion criteria between 2009 and 2019. Pelvic node macrometastases (≥2 mm) were confirmed in 54 patients (13.8%), and micrometastases (≥0.2 mm and <2 mm) in another 21 patients (5.4%). Ultrasonography had sensitivity 72.2%, specificity 94.0%, and area under the curve (AUC) 0.831 to detect pelvic macrometastases, while sensitivity 53.3%, specificity 94.0%, and AUC 0.737 to detect both pelvic macrometastases and micrometastases (pN1). Ultrasonography failed to detect pelvic micrometastases, with sensitivity 19.2%, specificity 85.2%, and AUC 0.522. There was no significant impact of body mass index on diagnostic accuracy. Metastases in para-aortic nodes (macrometastases only) were confirmed in 16 of 71 patients who underwent para-aortic lymphadenectomy. Ultrasonography yielded sensitivity 56.3%, specificity 98.2%, and AUC 0.772 to identify para-aortic node macrometastases. CONCLUSION: Ultrasonography performed by an experienced sonographer can be considered a sufficient diagnostic tool for pre-operative assessment of lymph nodes in patients with cervical cancer, showing similar diagnostic accuracy in detection of pelvic macrometastases as reported for other imaging methods (18F-fluorodeoxyglucose positron emission tomography/CT or diffusion-weighted imaging/MRI). It had low sensitivity for detection of small-volume macrometastases (largest diameter <5 mm) and micrometastases. The accuracy of para-aortic assessment was comparable to that for pelvic lymph nodes, and assessment of the para-aortic region should be an inseparable part of the examination protocol.
Keywords: mikrometastázy; Sensitivity and Specificity; senzitivita a specificita; Humans; lidé středního věku; Female; Aged; dospělí; Ultrasonography; nádory děložního čípku; senioři; lidé; Lymphatic Metastasis; Lymph Node Excision; lymfatické metastázy; Adult; Lymph Nodes; lymfatické uzliny; ženské pohlaví; ultrasonografie; Middle Aged; Retrospective Studies; předoperační péče; Uterine Cervical Neoplasms; lymfadenektomie; retrospektivní studie; Preoperative Care; Neoplasm Micrometastasis